TOPOLOGICAL DESCRIPTORS BASED MULTILINEAR REGRESSION ANALYSIS OF CARCINOGENIC PROPERTIES OF ANILINE DERIVATIVES: Life Sciences-Computational Chemistry - KHAN, S. A.; KUMAR VERMA, PRABHAT; TEWARI, ROLI (International Journal of Life Science and Pharma Research, 2022)
QSAR models of 73 derivatives of aniline, biphenylamine, naphthylamine and aminofluorenes which have carcinogenic property have been developed with the help of topological and energy descriptors such as log P calculated, connectivity index (order 1), valence connectivity index (order 0), shape index (order 1), dipole moment, solvent accessibility surface area and molar refractivity. The qualities of the models have been adjudged by the value of cross-validation and correlation coefficients evaluated by multi linear regression analysis. The best model has correlation coefficient 0.854963 and has been developed with the help of descriptors Log P calculated, connectivity index (order 1), valence connectivity index (order 0) and shape index (order 1).